The arousal-performance relationship - Wrisberg, C. A. (Quest, 1994)
One theme in discussing physical activity and stress is the relationship between emotional arousal and motor performance. Different research models have produced converging evidence for the notion that motor performance relates to a state of optimal arousal. Themes emerging from the literature and recommendations for future consideration are examined.